2011
DOI: 10.1007/s12088-011-0070-0
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and Characterization of Pediocin NV 5 Producing Pediococcus acidilactici LAB 5 from Vacuum-Packed Fermented Meat Product

Abstract: A potentially novel antimicrobial compound producing Pediococcus acidilactici LAB 5 was isolated from vacuum-packed fermented meat product. This compound was found active against some species of Enterococcus, Leuconostoc, Staphylococcus and Listeria, many of which are associated with food spoilage and food related health hazards. The strain was found to be a paired cocci which can utilize a broad range of carbohydrates and produce acid identical to the P. acidilactici and P. pentoseus. Since the antimicrobial … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
23
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(25 citation statements)
references
References 26 publications
2
23
0
Order By: Relevance
“…However, the residual antimicrobial activity of bacteriocin produced by MBSa3 at pH 10 was reduced to 26%, while that of bacteriocin produced by MBSa2 remained unchanged. As for stability at acidic pH, detected for the bacteriocins MBSa2 and MBSa3, several studies have shown that most bacteriocins are stable over a wide pH range, such as pediocin L50 (Cintas et al, 1995), piscicocin CS526 (Yamazaki et al, 2005), acidocin D20079 (Deraz et al, 2005) and pediocin NV5 (Mandal et al, 2011). Lower pH stability was described for plantaricin LP31 (Müller et al, 2009).…”
Section: Isolation Of the Bacteriocinogenic Strains And Characterizatmentioning
confidence: 99%
“…However, the residual antimicrobial activity of bacteriocin produced by MBSa3 at pH 10 was reduced to 26%, while that of bacteriocin produced by MBSa2 remained unchanged. As for stability at acidic pH, detected for the bacteriocins MBSa2 and MBSa3, several studies have shown that most bacteriocins are stable over a wide pH range, such as pediocin L50 (Cintas et al, 1995), piscicocin CS526 (Yamazaki et al, 2005), acidocin D20079 (Deraz et al, 2005) and pediocin NV5 (Mandal et al, 2011). Lower pH stability was described for plantaricin LP31 (Müller et al, 2009).…”
Section: Isolation Of the Bacteriocinogenic Strains And Characterizatmentioning
confidence: 99%
“…However, it is found to be active against the entire Gram positive bacteria tested (Tukel et al, 2007). Mandal et al (2011) also proved that pediocin NV5 had strong antimicrobial efficacy against L. mesenteroides, L. monocytogens and Enterococcus faecalis.…”
Section: Resultsmentioning
confidence: 88%
“…In the Disc Diffusion study, the anti-microbial activity of echinocystic acid (2) was evaluated against all the Gram-positive Bacillus subtilis, Listeria monocytogenes, Staphylococcus aureus and Gram-negative Escherichia coli, Salmonella typhimurium, Pseudomonas aeruginosa bacteria ( Table 1) [8][9][10][11]. It showed significant anti-microbial potential against the Gram-positive Bacillus subtilis, Listeria monocytogenes, Staphylococcus aureus and Gram-negative Salmonella typhimurium bacteria ( Figure 1).…”
Section: Resultsmentioning
confidence: 99%
“…In every two hours interval aliquot of culture (both treated and untreated) was withdrawn aseptically diluted serially with sterilized distilled water and plated into nutrient agar medium, incubated at 37°C for another 24 hrs. The colonies appeared were counted per ml of culture broth [7][8][9][10][11].…”
Section: Anti-microbial Mode Of Action Of Echinocystic Acid (2) On Grmentioning
confidence: 99%